A Preliminary investigation on Mural Flora of Jalpaiguri District of the Indian State West Bengal - Sarkar, Anup Kumar; Dey, Manas (Indian Forester, 2021)
Plants are well adapted to wide range of habitat. Some of them design their life processes for extra terrestrial survival on walls as an additional strategy to avoid completion and exclusion from the ecosystem are often considered as murophytes. Some of the murophytes often prove destructive to wall and similar construction and must be eradicated. The intensity of destruction is dependent on their frequency and their distribution on different position of wall. In this study the vascular plant flora growing on heritage buildings of Jalpaiguri district, West Bengal, India were identified and documented. For this study, some old buildings were selected as the study area. Among the vascular mural plants, 9 species of Pteridophyte and 68 of the angiosperm belonging to a total of 33 families of vascular flora were recorded. Maximum species diversity was noted in the substrate formed on a horizontal porous surface and cavities at ground level.